Cyclophilin a signaling induces pericyte-associated blood-brain barrier disruption after subarachnoid hemorrhage - Pengyu Pan; Hengli Zhao; Xuan Zhang; Qiang Li; Jie Qu; Shilun Zuo; Fan Yang; Guobiao Liang; John Zhang; Xin Liu; Haiyang He; Hua Feng; et al. (figshare, 2020)
Abstract Objective The potential roles and mechanisms of pericytes in maintaining blood–brain barrier (BBB) integrity, which would be helpful for the development of therapeutic strategies for subarachnoid hemorrhage (SAH), remain unclear. We sought to provide evidence on the potential role of pericytes in BBB disruption and possible involvement and mechanism of CypA signaling in both cultured pericytes and SAH models. Methods Three hundred fifty-three adult male C57B6J mice weighing 22 to 30 g, 29 CypA−/− mice, 30 CypA+/+ (flox/flox) mice, and 30 male neonatal C57B6J mice were used to investigate the time course of CypA expression in pericytes after SAH, the intrinsic function and mechanism of CypA in pericytes, and whether the known receptor CD147 mediates these effects. Results Our data demonstrated both intracellular CypA and CypA secretion increased after SAH and could activate CD147 receptor and downstream NF-κB pathway to induce MMP9 expression and proteolytic functions for degradation of endothelium tight junction proteins and basal membranes. CypA served as autocrine or paracrine ligand for its receptor, CD147. Although CypA could be endocytosed by pericytes, specific endocytosis inhibitor chlorpromazine did not have any effect on MMP9 activation. However, specific knockdown of CD147 could reverse the harmful effects of CypA expression in pericytes on the BBB integrity after SAH. Conclusions This study demonstrated for the first time that CypA mediated the harmful effects of pericytes on BBB disruption after SAH, which potentially mediated by CD147/NF-κB/MMP9 signal, and junction protein degradation in the brain. By targeting CypA and pericytes, this study may provide new insights on the management of SAH patients.
Keywords: Biochemistry; Cell Biology; Molecular Biology; Immunology; Biological Sciences not elsewhere classified; Information Systems not elsewhere classified; Science Policy; Hematology; Infectious Diseases; Plant Biology